Assessing NaV1.7 during tonic firing in pig C-nociceptors - Soares, Sabrina; Schmelz, Martin; Carr, Richard; Sohns, Kyra; Rukwied, Roman (PLOS ONE, 2025)
Assuming the voltage-gated sodium channel (VGSC) NaV1.7 facilitates action potential generation upon slow electrical depolarization, we investigated protoxin II and TTX to target VGSC sub-types and to assess their role in C-fiber excitability when stimulated with sinusoidal single 1 Hz pulse (500 ms) and repetitive 4 Hz stimuli. We performed ex vivo extracellular compound potentials (CAP) recordings of pig saphenous nerve and in vivo pig single nerve fiber (SNF) recordings of heat- mechanosensitive (“polymodal”) nociceptors (C-HT) and low- threshold mechanoresponsive C-fibers (C-LTMR) upon electrical 1 and 4 Hz sinusoidal stimulation, which evoke a discharge burst and a tonic response, respectively. Both toxins reduced C-CAP amplitudes and conduction velocity. Number of action potentials evoked by low-intensity phasic (1 Hz) or tonic (4 Hz) sinusoidal stimulation were reduced in C-HT nociceptors after protoxin. In C-LTMR fibers, protoxin reduced the number of action potentials to 4 Hz, but did not affect 1 Hz discharges. The toxins did not increase the delay of action potential initiation of C-CAPs or during SNF. Our results confirm the functional role of NaV1.7 to tonic supra-threshold electrical 4 Hz sinusoidal action potential firing in C-fibers. Protoxin reduced AP discharges to low-intensity phasic 1 Hz stimuli in C-HT nociceptors but not C-LTMR touch fibers. This finding suggests a differential functional role of NaV1.7 between C-fiber classes. Peripheral NaV1.7 blockade seems to increase the depolarization level required for C-nociceptor activation, and this might be relevant to target clinically ongoing pain.